2017
DOI: 10.5194/hess-2017-83
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Slope–Velocity–Equilibrium and evolution of surface roughness on a stony hillslope

Abstract: Abstract. Slope–velocity–equilibrium is hypothesized as a state that evolves naturally over time due to the interaction between overland flow and surface morphology, wherein steeper areas develop a relative increase in physical and hydraulic roughness such that flow velocity is a unique function of overland flow rate independent of slope gradient. This study tests this hypothesis under controlled conditions. Artificial rainfall was applied to 2 m by 6 m plots at 5 %, 12 %, and 20 % slope gradients. A series of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…As shown in Figure , the random roughness increased linearly from 1.57 to 2.67 mm with incorporated litter rate ( R 2 = 0.78). Previous studies found that surface roughness affected flow resistance through altering flow pathways and enhancing backwater (Dunkerley, ; Nearing et al, ). The regression analysis found that flow resistance increased linearly ( R 2 = 0.79), whereas flow velocity decreased linearly ( R 2 = 0.78), with soil surface roughness in this study.…”
Section: Resultsmentioning
confidence: 97%
“…As shown in Figure , the random roughness increased linearly from 1.57 to 2.67 mm with incorporated litter rate ( R 2 = 0.78). Previous studies found that surface roughness affected flow resistance through altering flow pathways and enhancing backwater (Dunkerley, ; Nearing et al, ). The regression analysis found that flow resistance increased linearly ( R 2 = 0.79), whereas flow velocity decreased linearly ( R 2 = 0.78), with soil surface roughness in this study.…”
Section: Resultsmentioning
confidence: 97%
“…Soils in semiarid areas that have been left bare after abandonment or land use change are one of the most important environmental factors driving soil erosion in arid and semiarid areas (Hueso‐González, Martínez‐Murillo, & Ruiz‐Sinoga, ; Kavian, Golshan, & Abdollahi, ; Nearing et al, ). Tillage and the overuse of herbicides causes a lack of vegetation cover that leaves soils uncovered and unprotected.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, rock fragments from the local parent materials could be a good option to reduce soil losses, and improve soil physical properties (van Wesemael et al ., ), soil biology (Certini et al ., ), soil moisture (Jiménez et al ., ), soil porosity and productivity (Nyssen et al ., ) at a low cost. Rock fragments may increase infiltration when not embedded and reduce soil losses because they can act as a protective cover (Nearing et al ., ). Most of the current research has been carried out under laboratory conditions with disturbed soil (Poesen et al ., ; Poesen & Lavee, ) or on forest and rangeland soil (Cerdà, ); however, we do not know the effect of rock fragment cover and disturbance in a managed vineyard setting.…”
Section: Introductionmentioning
confidence: 97%